College physics volume 2 - Serway, Raymond A.; Vuille, Chris (Cengage Learning, 2015)
Provides a clear strategy for connecting theories to a consistent problem-solving approach, carefully reinforcing this methodology throughout the text and connecting it to real-world examples.